A note on θ-generalized closed sets. (22nd February 2001) - Baker, C. W.
Abstract : The purpose of this note is to strengthen several results in the literature concerning the preservation ofθ -generalized closed sets. Also conditions are established under which images and inverse images of arbitrary sets areθ -generalized closed. In this process several new weak forms of continuous functions and closed functions are developed.